2021
DOI: 10.1177/14680874211045968
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of using detailed chemistry model for simulating direct injection spark ignition engine combustion during cold-start

Abstract: Computational Fluid Dynamics (CFD) modeling of gasoline spark-ignited engine combustion has been extensively discussed using both detailed chemistry mechanisms (e.g., SAGE) and flamelet models (e.g., the G-equation). The models have been extensively validated under normal operating conditions; however, few studies have discussed the capability of these models in capturing DISI combustion under cold-start conditions. A cold-start differs from normal operating conditions in various respects, such as (1) having h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…When a relatively high turbulent Schmidt number, 0.78 for example, was used in the SAGE model for cylinder 3, the combustion was weak and the pressure trace was under-predicted, which was similar to what Ravindran and Kokjohn 10 found for the laminar regime, stating: “The SAGE detailed chemistry model … under-predict the flame propagation speeds.” In this study, the turbulent Schmidt number was tuned and eventually set to 0.3 for cylinder 3 to match the experimental pressure traces, and then the same settings were applied in the simulations for the other three cylinders. The final results from the SAGE model are presented as the blue solid curves in Figure A1.…”
Section: Figure A1supporting
confidence: 68%
See 2 more Smart Citations
“…When a relatively high turbulent Schmidt number, 0.78 for example, was used in the SAGE model for cylinder 3, the combustion was weak and the pressure trace was under-predicted, which was similar to what Ravindran and Kokjohn 10 found for the laminar regime, stating: “The SAGE detailed chemistry model … under-predict the flame propagation speeds.” In this study, the turbulent Schmidt number was tuned and eventually set to 0.3 for cylinder 3 to match the experimental pressure traces, and then the same settings were applied in the simulations for the other three cylinders. The final results from the SAGE model are presented as the blue solid curves in Figure A1.…”
Section: Figure A1supporting
confidence: 68%
“…The problem possibly arose due to the effects on the flame of different turbulence levels for different cylinders and even for the same cylinder at different crank angles (due to the rapidly changing engine speed within a cycle). Ravindran and Kokjohn 10 extensively explored the use of the SAGE model in the laminar regime for cold-start conditions, and found that it presented challenges, under-predicting the flame propagation speeds, also noting that further study was needed to evaluate the turbulence-chemistry interactions in other regimes. Consequently, we decided to explore the implementation of the FES model – a model physically predicting the turbulence-flame interaction and also a model we have been working on for years – into the multi-dimensional simulations for cold start.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the PSR model was also promoted [18][19][20] for Reynolds-Averaged Navier-Stokes (RANS) simulations of premixed turbulent burning in combustion chambers of piston engines by assuming 19 weak temperature fluctuations in such chambers. Accordingly, the PSR model is widely used [21][22][23][24][25][26][27][28][29][30] in applied Computational Fluid Dynamics (CFD) research into turbulent burning in piston engines and other combustors. In particular, the PSR model is a default complex-chemistry model of flame-turbulence interaction in a popular CFD software such as Converge.…”
Section: Introductionmentioning
confidence: 99%